FAKTOR - FAKTOR YANG MEMPENGARUHI AUDIT DELAY DAN RELEVANSINYA TERHADAP TIMELINESS (Studi Empiris Pada Perusahaan Manufaktur di Bursa Efek Indonesia) - Abdullah Mubarok (Universitas Pamulang, 2017)
ABSTRACTThis study aimed to examine the effect of , the characteristics of the company and the audit committee of the audit delay and Timeliness. Characteristics of companies used in this study include profitability, solvency, size of the company. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange in 2011.2012 , 2013.2014 and 2015 .The sampling method in this research is purposive sampling. The analysis technique used is multiple linear regression. The analysis showed profitability , solvency , and company size significantly affect audit delay at different levels. Variable audit committee did not significantly affect audit delay. Analysis of the timeliness show profitability and company size significantly affect timeliness. Variable solvency and audit committee no significant effect on timeliness.